Beetles - Sexton, Colleen A., 1967- (Minneapolis, MN : Bellwether Media, 2007)
"Simple text accompanied by full-color photographs give an upclose look at beetles. Intended for kindergarten through third grade students"--Provided by publisher.
Where the beetle lives -- The beetle's head -- The beetle's legs -- The beetle's wings -- Many kinds of beetles.
Includes bibliographical references and index.
Keywords: Beetles -- Juvenile literature